A Re-conceptualization of Student-Athlete Education: Utilizing Critical Theory to Eliminate Perceived Conflict - Meyer, Barbara B. (My University, 1999)
The purposes of this qualitativestudy were to examine how Division I football and basketball players were able to obtain a balanced, comprehensive college education, and to explore specific factors that enhanced the overall quality and symmetry of their experience. The participants in the study consisted of 26 former male letter-winning football (n=20) and basketball (n=6) players. Nineteen percent of the participants were African-American and 81% were Anglo-American. Approximately 30% of the men in the sample had played their respective sports at the professional level. Results of this study highlighted the inability of role theory to explain and manage issues related to student-athlete education, and suggested that critical theory may best explain how to secure a balanced, comprehensive education. Implications for personnel who provide personal support to student-athtetes were discussed.
Keywords: sex/gender; demographics; football; basketball; college experience; coaches